Pemberdayaan remaja melalui edukasi gizi sebagai upaya pencegahan stunting sejak dini - Hasriani, St. Hasriani; Pratiwi, Wilda Rezki; Qardhawijayanti, Suci; Murtini, Murtini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Indonesia has one of the highest stunting rates in the world, with nearly 25% of Indonesian children under five affected by stunting. The Nutritional Status Research (SSGI) from the Indonesian Ministry of Health revealed that in 2021, stunting affected 24.4% of children under five across the country. Providing adequate nutrition during adolescence and educating women about stunting is a strategy to prevent anemia and contribute to preventing future stunting. Purpose: To increase knowledge about nutrition and stunting among adolescents as an effort to prevent stunting from an early age. Method: This activity was held on September 16, 2025, in Amparita Village, Sidenreng Rappang Regency, with the theme